Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

We have been discussing pmf. Can someone please show me

A. That the pmf for a binomial random variable sums to 1

B. That the pmf for a geometric random variable sum to 1

So I may see the difference

share|cite|improve this question
What do you mean by A and 1 b? For any discrete random variable, the sum of the pmf over all possible values is $1$. This is because the total probability (i.e. the probability of the whole sample space) is always $1$. – Robert Israel Sep 30 '12 at 23:59
up vote 2 down vote accepted

A. You have to show $$\sum_{i=0}^n {n \choose i}p^i(1-p)^{n-i}=1$$ but the left hand side is $$(p+(1-p))^n=1.$$

B. Depending on your definition, you have to show $$\sum_{i=0}^\infty p(1-p)^{i}=1 \text{ or } \sum_{j=1}^\infty p(1-p)^{j-1}=1 $$ and they are clearly the same sums if you replace $i$ by $j-1$.

The geometric series $\sum_{i=0}^\infty x^i = \frac{1}{1-x}$ for $|x|\lt 1$, so (taking the former) $$p\times \sum_{i=0}^\infty (1-p)^{i}=p\times \dfrac{1}{1-(1-p)}=1.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.